ACCOUNTING AND SOCIAL SECURITY PAYMENT TRANSFERRED TO THE NATIONAL INSTITUTE OF SOCIAL SECURITY (INSS): A PERIODIC ACCOUNTING SAGA - Gomes da Conceição, Alessandra; Eduardo Mello Brito, Rubem; Jorge Ladeira dos Santos, Waldir (Revista Gênero e Interdisciplinaridade, 2022)
This article will aim to study the cost accounting in the issue of accounting deduction to the National Institute of Social Security (INSS). In this sense, the problem to be discussed is how and which accounting fundamentals are necessary for this type of operation to be carried out in the accounting context by business institutions. Therefore, a bibliographic survey of the most recent productions was carried out on the topic addressed. From the reading of specific texts related to the theme, it was understood that in order to obtain a coherent understanding of the general object of this work there is a need to explain brief concepts about general accounting, cost accounting and accounting cost, to, finally, explain and delimit the object of this work: the accounting of costs and the sending of the payment to the INSS.